Poly (phenazine 2, 3-diimino(pyrrole-2-yl)) as Redox Stimulated Actuator Material for Selected Organic Dyes. Issue 14 (1st January 2017) - Iftikhar, Faiza Jan; Shah, Afzal; Baker, Priscilla G. L.; Iwuoha, Emmanuel I.; Haider, Adnan; Zia, Muhammad Abid; Nisar, Jan; Siddiq, Muhammad; Shah, Aamir Hassan
Abstract : The use of polymers as actuator materials has been reported extensively in the recent years. Polymers based actuators have specifically drawn attention of scientists as valves for drug delivery applications. This spurred us on for studying the actuation properties of doped polypyrrole based phenazine derivative and its drug delivery application using cyclic voltammetry, square wave voltammetry, UV-Vis spectroscopy and electrochemical impedance spectroscopy. We investigated the flexibility provided by molecular hinged linking molecule (phenazine) in an accordion type polymer- poly(phenazine 2, 3-diimino(pyrole-2-yl)) doped with polyvinyl sulfonic acid (PVSA) with the objective of getting insights about generation of conformational changes required for the introduction of large space volume for actuation. The actuation thus developed was tested on redox dyes such as pyrocatechol violet and methyl orange for their controlled adsorption and release from the doped polymeric material to assess its potential as a smart drug delivery device.